A Study of Women’s Voices: Breaking the Silence: Exploring Diasporic Elements in Chitra Banerjee Divakaruni's Works (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Chitra Banerjee Divakaruni is a productive writer who has composed many articles, sonnets, short stories and novels. In her works she has offered voice to foreigner Indian women. In this investigation I will attempt to break down various issues women face and disposition of Divakaruni as a postcolonial women's activist author. Her novels and short stories that represent instructed, inflexible, rationally solid and insubordinate female characters who don't waver to free themselves from male haughtiness. Indian conceived novelist Chitra Banerjee Divakaruni presently lives in Houston, Texas. Her novels give new points of view to contemporary women's writing. In them we have women who either live abroad or happen to visit India. These women are no uncertainties molded by the Indian childhood however have transcended the customary limitations. They are torn amongst old and new qualities. They question the idea of their lives, and their roles as moms, spouses, daughters and experts. This mindfulness drives them to reconsider about their own lives as women and ingrains in them the certainty and quality to proceed. Chitra Banerjee Divakaruni centers around the diasporic cognizant ness of Indian women got between two contradicting universes. Chitra Banerjee Divakruni is one of the real Indian diaspora writers in English. She is the artist and in addition novelist. She has won esteemed honors like American Book Award, Hackney Literary Award and Pen Syndicated Fiction Award for her commitment to writing. The hidden subject of her works is diasporic experience. This article expects to investigate the diasporic components in The Mistress of Spices.